Albert Camus’s Ethics of Revolution as a Model for Ethical Thinking on Violent Revolutions for Catholics - Onah, Gideon Owogeka (Religions, 2024)
In this paper, I propose an account of Camus’s ethics in which violent revolutions are never morally permissible but nonetheless acceptable or necessary. My main thesis in this paper is that Camus’s ethics of revolution and my defence of it, particularly the non-moral account of the permissibility of violent revolutions it comprises, can shed light on the reasonableness of participating in and supporting violent revolutions to some Catholics and the broader Christian community. My account of Camus’s ethics of revolution and argument for its tenability will be compelling to some Catholics because they affirm their intuition that violent revolutions are morally untenable and show why it is nevertheless reasonable.